Peran Organisasi Kerjasama Islam (OKI) Dalam Menangani Konflik Rohingya di Myanmar Tahun 2016 – 2017 - Setiani, Revina Putri; Setiawan , Asep; Gunanto , Djoni; Effendi, Cecep (Journal of Comprehensive Science, 2024)
The Rohingya ethnic group in Myanmar has experienced systematic discrimination and marginalization since 1962, culminating in denial of citizenship and restrictions on access to basic services. The governments of Myanmar and Bangladesh have both refused to recognise the Rohingya as citizens, leaving them in a stateless state. The escalating ethnic conflict, especially after Myanmar's military offensive in 2017, forced hundreds of thousands of Rohingya to flee to Bangladesh and other countries. Reports from the UN and human rights organizations indicate ethnic cleansing, including killing, rape and torture of the Rohingya. Despite international pressure, Myanmar's government, including leader Aung San Suu Kyi, denies any repression. The Organization of Islamic Cooperation (OIC) is acting as an initiator and mediator in diplomatic efforts to resolve this conflict, but major challenges remain in creating sustainable and equitable solutions for the Rohingya. This study aims to examine the role of the Organization of Islamic Cooperation (OIC) in the Rohingya conflict in Myanmar in 2016 – 2017. In this study, the concepts of international organizations and human security are used in analyzing the role of the OIC in resolving the conflict. This study uses qualitative methods and descriptive research types. This study concludes that there are four roles of the OIC, the first and second as initiators and mediators, where most of the OIC's role here is to hold meetings with OIC members to provide assistance to Rohingya refugees. The third is humanitarian, providing assistance for the human rights of the Rohingya, and the fourth is the facilitator, where the OIC, other international organizations, and OIC member countries work together to provide basic assistance and facilities such as education and health to the Rohingya.